2015
DOI: 10.1212/wnl.0000000000001514
|View full text |Cite
|
Sign up to set email alerts
|

Poststroke suicide attempts and completed suicides

Abstract: Objective: We examined attempted and completed suicides after stroke to determine whether they were associated with socioeconomic status, other patient characteristics, or time after stroke.Methods: This nationwide cohort study included stroke patients from Riksstroke (the Swedish Stroke Register) from 2001 to 2012. We used personal identification numbers to link the Riksstroke data with other national registers. Suicide attempts were identified by a record of hospital admission for intentional self-harm (ICD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
52
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 23 publications
9
52
1
1
Order By: Relevance
“…In their article "Poststroke suicide attempts and completed suicides: A socioeconomic and nationwide perspective," 1 Dr. Eriksson and colleagues focused on suicide after a serious brain injury (stroke). The authors work at Umea University in Sweden and the study was supported by the Swedish Council for Health and the Swedish Research Council.…”
Section: Suicide After Strokementioning
confidence: 99%
See 1 more Smart Citation
“…In their article "Poststroke suicide attempts and completed suicides: A socioeconomic and nationwide perspective," 1 Dr. Eriksson and colleagues focused on suicide after a serious brain injury (stroke). The authors work at Umea University in Sweden and the study was supported by the Swedish Council for Health and the Swedish Research Council.…”
Section: Suicide After Strokementioning
confidence: 99%
“…One thought is that younger people with stroke are much more likely to attempt or commit suicide than older adults. 1 However, many other factors may contribute, including a person's cultural and religious upbringing. Socioeconomic factors, income, and education may also play a role.…”
Section: Why Was the Study Done?mentioning
confidence: 99%
“…The risk was highest during the first 2 years after stroke. [14] The other authors like Alajbegovic et al reported post-stroke depression to be more common in females. [15] Lastly the difference in the nature of depression is reported by Paradiso S who in his study found that in men major depression was associated with greater impairment in activities of daily living, and greater severity of depression was associated with greater impairment in daily activities and social functioning while in women, greater severity of depression was associated with prior diagnosis of psychiatric disorder and cognitive impairment.…”
Section: Discussionmentioning
confidence: 96%
“…This is mainly due to the high number of stroke patients in comparison to the limited number of therapists [23], [24], [31]. Therapy itself should also be more engaging to the patient, instead of the conventional dull exercises.…”
Section: Outlook Of Stroke Therapymentioning
confidence: 99%